UniSAFE Survey - Gender-based violence and institutional responses - Lipinsky, Anke (GESIS, 2022)
The UniSAFE survey collected data on experiences of gender-based violence, including sexual harassment, among students and employees in 46 higher education institutions and research institutions in 15 countries in the period 17.01.-01.05.2022 (n= 42,186). Factors of influence and effects of gender-based violence are part of the survey. The prevalence data refers to six forms of violence, based on the four forms of gender-based violence described in the Council of Europe's Istanbul Convention: physical violence, psychological violence, economic violence and sexual violence. In addition, the survey includes two other forms of violence: sexual harassment and digital violence. The results of the UniSAFE survey add to the current knowledge base on the occurrence of gender-based violence by individuals (micro-level) in the context of science and research. The UniSAFE survey is part of an EU-funded study (grant number 101006261) with several qualitative and quantitative data collections.